FOOTPRINTS study protocol: rationale and methodology of a 3-year longitudinal observational study to phenotype patients with COPD. Issue 3 (22nd March 2021) - Crapo, James; Gupta, Abhya; Lynch, David A; Vogel-Claussen, Jens; Watz, Henrik; Turner, Alice M; Mroz, Robert M; Janssens, Wim; Ludwig-Sengpiel, Andrea; Beck, Markus; Langellier, Bérengère; Ittrich, Carina; et al.
Abstract : Introduction: A better understanding is needed of the different phenotypes that exist for patients with chronic obstructive pulmonary disease (COPD), their relationship with the pathogenesis of COPD and how they may affect disease progression. Biomarkers, including those associated with emphysema, may assist in characterising patients and in predicting and monitoring the course of disease. The FOOTPRINTS study (study 352.2069) aims to identify biomarkers associated with emphysema, over a 3-year period. Methods and analysis: The FOOTPRINTS study is a prospective, longitudinal, multinational (12 countries), multicentre (51 sites) biomarker study, which has enrolled a total of 463 ex-smokers, including subjects without airflow limitation (as defined by the 2015 Global Initiative for Chronic Obstructive Lung Disease (GOLD) strategy report), patients with COPD across the GOLD stages 1–3 and patients with COPD and alpha1-antitrypsin deficiency. The study has an observational period lasting 156 weeks that includes seven site visits and additional phone interviews. Biomarkers in blood and sputum, imaging data (CT and magnetic resonance), clinical parameters, medical events of special interest and safety are being assessed at regular visits. Disease progression based on biomarker values and COPD phenotypes are being assessed using multivariate statistical prediction models. Ethics and dissemination: The study protocol was approved by the authorities and ethics committees/institutional review boards of the respective institutions where applicable, which included study sites in Belgium, Canada, Denmark, Finland, Germany, Japan, Korea, Poland, Spain, Sweden, UK and USA; written informed consent has been obtained from all study participants. Ethics committee approval was obtained for all participating sites prior to enrolment of the study participants. The study results will be reported in peer-reviewed publications. Trial registration number: NCT02719184 .